Combining conventional therapy with immunotherapy: A risky business?. (May 2019) - Coosemans, A.; Vankerckhoven, A.; Baert, T.; Boon, L.; Ruts, H.; Riva, M.; Blagden, S.; Delforge, M.; Concin, N.; Mirza, M.R.; Ledermann, J.A.; du Bois, A.; et al.
Abstract: Because of the failure of immunotherapy as single agent in a number of cancers, current clinical trials are focusing on combining immunotherapy with other therapies. The most frequently chosen combination for immunotherapy is chemotherapy. However, almost no preclinical data on this combination is available. Some studies even showed a dismal effect of combining chemotherapy with immunotherapy. Taken into account that each of the therapies chosen in a combination will influence the cancer cells but also immune effector cells as well as immunosuppressive cells, and that these three partners will also interact with each other, launching a combination to the patient without proper immune monitoring and preclinical evidence might be devastating. Highlights: Manipulating the order of chemotherapy and immunotherapy can reduce survival. Thorough immune monitoring prior and during combination treatments is necessary. More preclinical work is needed before applying combinatorial therapies to patients.